Do charismatic species groups generate more cultural ecosystem service benefits? - McGinlay, James; Parsons, David J.; Morris, Joe; Hubatova, Marie; Graves, Anil; Bradbury, Richard B.; Bullock, James M. (Elsevier, 2017)
The relationship between nature and cultural ecosystem service (CES) benefits is well accepted but poorly understood, as is the potential role of biodiversity in the relationship. By means of a public questionnaire survey in Wiltshire, UK, the relationship between the presence of a range of common species groups, species group ‘charisma’, group abundance in the landscape, and the benefit that people felt that they derived from the species groups was investigated for a lowland multifunctional landscape. Findings showed that species group charisma influenced the benefit reported by respondents for current abundance levels, and influenced their response to potential increases or decreases in abundance. Respondents reported high levels of benefit from species groups hypothesised to be charismatic (birds, flowering plants, butterflies) and there was high consistency in the pattern of response. Respondents reported less benefit from groups hypothesised to be less charismatic (beetles/bugs, brambles and nettles), the latter response patterns showing much greater variation. These results could be used to promote a more holistic understanding of the value of biodiversity by educating and informing the public so that they derive benefit not just from the charismatic, but also from the everyday, the commonplace and less obviously charismatic species.